The Bulgarian mission of Tadeusz Stanislaw Grabowski in the years 1915–1918 in his publications in the weekly magazine ”Wiadomości Polskie” - Rubacha, Jarosław (Balcanica Posnaniensia. Acta et studia, 2017)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The outbreak of World War I inspired the Supreme National Committee to take action for the popularization of the political aims of Poles in Europe. The network of information agencies was created for this purpose. One of the agencies was the press office in Sofia with T. S. Grabowski at the forefront. The agency not only provided information about events in Poland, but also promoted the Polish culture and created a basis for the future bilateral Polish-Bulgarian cooperation.